Study of the robber flies (Diptera: Asilidae) in East and West Azerbaijan provinces of Iran, with two new species records for the country - Rahman Mohammadi; Samad Khaghaninia; Dmitry Astakhov (Journal of Insect Biodiversity and Systematics, 2017)
Based on specimens collected from East and West Azerbaijan provinces during 2014–2016, fourteen species of the family Asilidaeare collected and identified. Two of them, e.g. Dysmachus transcaucasicus Richter, 1962; Saropogon megriensis Richter, 1966 are recorded from Iran for the first time. All species are listed along with their geographic distributions. Diagnostic characters as well as supplementary photos of new records are provided.